2018
DOI: 10.12816/0045639
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge about Liver Cirrhosis among Saudi Population

Abstract: Background: Liver cirrhosis is chronic disease associated with high mortality and morbidity rates all over the world. Objectives: evaluating the knowledge of adult Saudi population toward liver cirrhosis. Methods: A qualitative study was conducted in Kingdom of Saudi Arabia among 820 Saudi subjects during the period from October to December 2017. Results: A total of 820 subjects were enrolled in the study. All the subjects had good knowledge regarding the definition of liver cirrhosis. The majority of subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In a study conducted in Saudi Arabia regarding liver cirrhosis, which is a part of CLD, 54% of Saudi population had good knowledge while 46% had poor knowledge [12]. The most probable reason for majority of their population having good knowledge is the higher literacy rate as compared with that of Pakistan, which supports our results, i.e., majority of the people having poor knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…In a study conducted in Saudi Arabia regarding liver cirrhosis, which is a part of CLD, 54% of Saudi population had good knowledge while 46% had poor knowledge [12]. The most probable reason for majority of their population having good knowledge is the higher literacy rate as compared with that of Pakistan, which supports our results, i.e., majority of the people having poor knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…In the middle-eastern regions, nearly 10% of the population suffers from the infections of hepatitis-B virus (HBV), and more than 2% of the population is infected with the hepatitis-C virus (HCV), which indicates high prevalence rates of these liver-related infections, which is in addition to other liver-based disorders, including the symptomatic conditions of hyperbilirubinemia-related yellow-coloration, commonly referred to as jaundice. Liver disorders are a serious global healthcare concern [ 2 ], and the demand for valuable health-care resources, as well as attention in curtailing them, is huge [ 3 , 4 ]. The common risk factors, such as obesity, diabetes, hypercholesterolemia, and excessive drinking also make the situation further alarming [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Max van Manen (1990) also marked that Phenomenology as a reply to one how orients to lived experience and the question the way to one experiences the world [29]. One of the study reported that 72.2% affected people had college degree [14] but another study mentioned that 67.5% of patients had at least high school degree [31]. In this study, 55% patients have similar educational qualification.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, one qualitative study was conducted among community people in Saudi Arabia, they were not patients but they had good knowledge regarding the meaning or definition of the Cirrhosis of liver. Because most of them were higher educated [14]. Open Journal of Gastroenterology…”
Section: Socio-demographic Characteristics Of Cirrhosis Of Livermentioning
confidence: 99%
See 1 more Smart Citation